A review on nanoparticles as a catalyst for biodiesel production - Babulla Shaik; A. Muni Kumari (Results in Chemistry)
Biofuels offer a cleaner, greener alternative to fossil fuels, helping cut greenhouse gas emissions and reducing our reliance on finite energy sources. But producing biodiesel the traditional way isn't always easy—it can be costly, inefficient, and sometimes even harmful to the environment. That's where nanocatalysts come in. Thanks to their tiny size, high reactivity, and durability, they're emerging as game-changing catalysts for biodiesel production. Take Fe₃O₄@Al₂O₃ nanocatalysts, for example, they've achieved an impressive 93 % biodiesel yield in just an hour and kept over 80 % of their effectiveness even after seven uses. Similarly, adding copper to nanoferrite catalysts has boosted biodiesel yields by up to 85 % compared to regular versions. This review dives into the world of metal, metal oxide, and composite nanocatalysts, exploring how they're made, how they work, their environmental footprint, and how well they can be reused. It also looks ahead, discussing how researchers can fine-tune these catalysts to make them more efficient, affordable, and eco-friendly while tackling challenges like toxicity and large-scale production. The findings underscore the transformative potential of nanotechnology in enabling more sustainable, efficient, and scalable biodiesel manufacturing.